MENGAJI TILAWATI DI ERA PANDEMI DI TPQ SABILUNNAJAH DESA KESENENG KECAMATAN MOJOTENGAH - Miftakhul Fajrin; M Yusuf Amin Nugroho (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
Al-Qur'an is sustainable until the Day of Resurrection, as well as learning the Qur'an must be endeavored to sustainably be given to mankind regardless of the circumstances, including the Covid-19 pandemic situation. This paper aims to analyze the learning of the Qur'an in the Covid-19 era in keseneng mojotengah, Wonosobo. The formulation of this study focuses on discussing how the learning method of the Qur'an in the Covid-19 era in gesing, Southeast Aceh, the objectives of learning the Koran are still prioritized in the Covid-19 era and the learning objectives of the Qur'an are given to anyone.